Implementation of Islamic Education Curriculum Development in Al-Ulum Islamic School Medan - Widya Ayuningsih; Syafaruddin Syafaruddin; Amiruddin MS (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The objectives of this research are: (1) to find out the planning of developing Islamic education curriculum in Al-Ulum Islamic School Medan, (2) to know the implementation of Islamic Education curriculum development in Al-Ulum Islamic School Medan, and (3) to find out the evaluation of the development of Islamic Education Curriculum in Al-Ulum Islamic School Medan. The approach taken in this study is a qualitative approach. This means that the data collected is not in the form of numbers, but data that comes from interviews, observations of personal documents, notes, memos and other official documents. The results of this study are: (1) planning the development of Islamic Education curriculum in the Al-Ulum Islamic School in Medan carried out through 3 stages: (a) the development of institution-level programs, (b) the development of programs for each subject, and (c) the development of teaching programs in the classroom, (2) the implementation of the development of Islamic Education curriculum in Al-Ulum Islamic School Medan carried out through two types of curriculum namely the intracuricular and extracurricular curriculum, and (3) the evaluation of the development of Islamic Education curriculum in Al-Ulum Islamic School Medan namely by holding monthly meetings and also the supervision of teachers. and conduct comparative study activities to other schools in and outside the city.